Implementing E-Health through CHI: A Very Canadian Solution to a Very Canadian Problem - Tom Daniels (McMaster University Library Press, 2014)
Canada Health Infoway (CHI) was established as an arms-length body by the federal government in 2001 to provide funding to provinces for the development of interoperable e-health systems. CHI was established in response to a number of reports calling on the government to act to make use of technological advances to improve health care quality and provide more rigorous data. In addition to these explicit goals, through establishing CHI the federal government also sought to avoid potential criticism if the implementation of e-health failed, increase its own popularity ahead of the 2000 election and subtly redistribute wealth between the provinces. The paper suggests that the major influence behind the policy to establish CHI came from Canadian institutions and the fact that the federal government was hamstrung by the Canadian Constitution and Canada Health Act. Evaluation of the reform shows that progress has been made by CHI in implementing e-health solutions, but that Canada still lags behind other comparable health systems in the use of technologies. SWOT analysis of the CHI implementation highlights the criticism that CHI could stifle provincial innovation but recognizes that it also offers the opportunity for best practice dissemination across Canada and ensures that ring-fenced funding is available for e-health implementation across the provinces. In conclusion, the paper suggests that, because of constitutional constraints, the federal government was limited in options to implement e-health and that CHI represents a fair compromise.